2016
DOI: 10.7759/cureus.498
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-analysis of Chiropractic Care and Cervical Artery Dissection: No Evidence for Causation

Abstract: BackgroundCase reports and case control studies have suggested an association between chiropractic neck manipulation and cervical artery dissection (CAD), but a causal relationship has not been established. We evaluated the evidence related to this topic by performing a systematic review and meta-analysis of published data on chiropractic manipulation and CAD.MethodsSearch terms were entered into standard search engines in a systematic fashion. The articles were reviewed by study authors, graded independently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
68
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 30 publications
0
68
0
2
Order By: Relevance
“…Therefore, inaccurate assignment of exposure to the putative trigger (SMT) is possible, and recall bias may have contributed to their data given the study design. A recent meta-analysis pooling all published studies found a nearly two fold higher risk of CAD associated with SMT [33]. But when limited to the 4 studies with imaging confirmation of cervical arterial dissection as the endpoint, SMT was associated with a significant 4-fold increase in risk [34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, inaccurate assignment of exposure to the putative trigger (SMT) is possible, and recall bias may have contributed to their data given the study design. A recent meta-analysis pooling all published studies found a nearly two fold higher risk of CAD associated with SMT [33]. But when limited to the 4 studies with imaging confirmation of cervical arterial dissection as the endpoint, SMT was associated with a significant 4-fold increase in risk [34].…”
Section: Discussionmentioning
confidence: 99%
“…Given the prevalence of SMT exposure (~8 % of adults and ~3 % of children annually) [38], even a modest increase in risk of dissection associated with SMT [33] could translate to thousands of avoidable dissections and strokes worldwide each year. So, on a population level, even a modest association between SMT and CAD could translate into a meaningful impact on public health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest that the most plausible explanation for the association between visits to chiropractors and VAD is that CMT is not a cause of VAD [11], but rather that patients who experience neck pain and/or headache resulting from the arterial dissection seek the services of a practitioner of CMT for relief of this pain, then go on to develop a stroke after this visit, independent of the CMT. This would also explain the similar associations of stroke between chiropractic and PCP patients; some patients with these symptoms will see their PCP and others a chiropractor.…”
Section: Discussionmentioning
confidence: 99%
“…Control for what Church et al [11] refer to as “interviewer bias.” Because of the highly publicized nature of many case reports and anecdotes about the relationship between visits to practitioners of CMT and stroke, emergency department physicians and neurologists who see patients with posterior circulation stroke may be more likely to attribute such a stroke to VAD resulting from CMT. Thus, many cases may be erroneously coded as VAD in the administrative database.…”
Section: Discussionmentioning
confidence: 99%